2014
DOI: 10.1002/chem.201303355
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Benzyl Alcohol and Carbon Monoxide Using Gold Nanoparticles Supported on MnO2 Nanowire Microspheres

Abstract: MnO2 was synthesised as a catalyst support material using a hydrothermal method. This involved reacting MnSO4⋅H2O and (NH4)2S2O8 at 120 °C for a range of crystallisation times, which affords control over the morphology and phase composition of the MnO2 formed. Gold was deposited on these supports using sol-immobilisation, impregnation and deposition precipitation methods, and the resultant materials were used for the oxidation of benzyl alcohol and carbon monoxide. The effect of the support morphology on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…The selection of support materials and preparation methods plays a key roles in determining the catalytic activity of supported noble metal catalysts. Transition metal oxides, such as Fe x O y , Co 3 O 4 ,, MnO x and TiO 2 , exhibit great potential as support materials for noble metal NPs due to their high chemical and thermal stabilities, wide abundance, and low cost . In addition, some oxides can further enhance the overall catalytic activity of the catalysts by enabling CO to react with the adsorbed oxygen species on their surface and the intermediate or oxygen provided by the support .…”
Section: Introductionmentioning
confidence: 99%
“…The selection of support materials and preparation methods plays a key roles in determining the catalytic activity of supported noble metal catalysts. Transition metal oxides, such as Fe x O y , Co 3 O 4 ,, MnO x and TiO 2 , exhibit great potential as support materials for noble metal NPs due to their high chemical and thermal stabilities, wide abundance, and low cost . In addition, some oxides can further enhance the overall catalytic activity of the catalysts by enabling CO to react with the adsorbed oxygen species on their surface and the intermediate or oxygen provided by the support .…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of photocatalytic organic synthesis, if the PEC-generatedh ighly active oxygen or hydrogen species directly participates in the chemical oxidation or reduction reaction, ap romisings trategy based on PEC water-splitting/organic-synthesis coupling can be achieved. The following advantages are expected in this new reaction system:f irstly,P EC facilitates the charges eparation owingt ot he introductiono f ab ias, giving rise to high catalytic efficiency;s econdly,h ighlyactiveo xygen or hydrogen species originating from PEC water splitting serves as clean and cost-effective oxidant or reducing agent, without the consumption of noxiouso rganic counterparts.I na ddition, this PEC water-splitting/organic-synthesis coupling process may occur at normalp ressure andt emperature in aqueousm edia, so as to achieve ag reen synthesis pathway.The transformation of alcohols to corresponding aldehydes in liquid-phase oxidation has been well-developed previously by using variousc atalysts, including noble metal catalysts (e.g., Pd, Au) [31][32][33][34] and non-precious-metalc atalysts. [35,36] Differently, here we report photoelectrochemical oxidation of alcohols in the photoanode with H 2 generated in the cathode, which couples PEC water splitting with selectiveo xidation reaction of organic molecules.…”
mentioning
confidence: 99%
“…The transformation of alcohols to corresponding aldehydes in liquid-phase oxidation has been well-developed previously by using variousc atalysts, including noble metal catalysts (e.g., Pd, Au) [31][32][33][34] and non-precious-metalc atalysts. [35,36] Differently, here we report photoelectrochemical oxidation of alcohols in the photoanode with H 2 generated in the cathode, which couples PEC water splitting with selectiveo xidation reaction of organic molecules.…”
mentioning
confidence: 99%
“…[2][3][4] Among the varioust ransition-metal catalysts that have shown activity for this aerobic oxidation, those based on supported metal nano-particles (NPs) are among the most efficient and selective ones, exhibiting al arge scope under aw ide range of experimentalc onditions. [2,3,5,6] In this type of heterogeneousc atalysts, one of the most important roles of the support is to stabilize the dimensions of gold NPs, minimizing their growth by strong metal-support interactions. [2,7,8] Extensive study of the literature has shown that the catalytic activity of metal NPs for this aerobic oxidation decreases as the particles ize increases.…”
Section: Introductionmentioning
confidence: 99%